Sak4 of Phage HK620 Is a RecA Remote Homolog With Single-Strand Annealing Activity Stimulated by Its Cognate SSB Protein - Hutinet, Geoffrey; Besle, Arthur; Son, Olivier; McGovern, Stephen; Guerois, Raphaël; Petit, Marie-Agnès; Ochsenbein, Françoise; Lecointe, François (Frontiers in Microbiology, 2018)
Bacteriophages are remarkable for the wide diversity of proteins they encode to perform DNA replication and homologous recombination. Looking back at these ancestral forms of life may help understanding how similar proteins work in more sophisticated organisms. For instance, the Sak4 family is composed of proteins similar to the archaeal RadB protein, a Rad51 paralog. We have previously shown that Sak4 allowed single-strand annealing in vivo, but only weakly compared to the phage λ Redβ protein, highlighting putatively that Sak4 requires partners to be efficient. Here, we report that the purified Sak4 of phage HK620 infecting Escherichia coli is a poorly efficient annealase on its own. A distant homolog of SSB, which gene is usually next to the sak4 gene in various species of phages, highly stimulates its recombineering activity in vivo. In vitro, Sak4 binds single-stranded DNA and performs single-strand annealing in an ATP-dependent way. Remarkably, the single-strand annealing activity of Sak4 is stimulated by its cognate SSB. The last six C-terminal amino acids of this SSB are essential for the binding of Sak4 to SSB-covered single-stranded DNA, as well as for the stimulation of its annealase activity. Finally, expression of sak4 and ssb from HK620 can promote low-level of recombination in vivo, though Sak4 and its SSB are unable to promote strand exchange in vitro. Regarding its homology with RecA, Sak4 could represent a link between two previously distinct types of recombinases, i.e. annealases that help strand exchange proteins and strand exchange proteins themselves.